Prognostic value and immune infiltration of the gasdermin family in lung adenocarcinoma - Peng, Lu-Shan; Duan, Sai-Li; Li, Run-Qi; Wang, Dan; Han, Ying-Ying; Huang, Tao; Yu, Yu-Pei; Ou, Chun-Lin; Wang, Jun-Pu (Frontiers in Oncology, 2022)
Background: The GSDM family includes six members, GSDMA, GSDMB, GSDMC, GSDMD, GSDME (DFNA5), and PJVK (Pejvakin, DFNB59), which can induce pyroptosis, thereby regulating the tumorigenesis of various cancers. However, the clinical characteristics and role of the GSDM family in LUAD are not well understood. Methods: In this study, several important bioinformatics databases were used to integrate the analysis of the expression, prognostic value, and immune infiltration of GSDMs in LUAD. These databases include UALCAN, DiseaseMeth, GEPIA, THPA, cBioPortal, TIMER, WebGestalt, STRING database, and Cytoscape. Results: The findings from the UALCAN database revealed that the expression of all six GSDMs based on the tumor stage in LUAD was increased. Additionally, the DiseaseMeth database showed that the methylation levels of GSDMA, GSDMB, GSDMC, and GSDMD were decreased. The expression of six GSDMs was related to shorter overall survival in patients with LUAD, according to the GEPIA database. The cBioPortal database was further used to explore the alteration rate and correlated genes in LUAD. Subsequently, these genes were subjected to functional enrichment and protein-protein interaction network analyses. We identified that the GSDM family regulate several signaling pathways, including immune-associated signaling pathways. According to tumor-infiltrating immune cell analysis from the TIMER database, GSDM family members are associated with the infiltration of important immune cells and their signature markers. Conclusion: GSDM family may be prognostic markers and novel strategies for the treatment of LUAD.